2017
DOI: 10.1097/md.0000000000008123
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of combined intra-articular and intravenous tranexamic acid for blood loss in primary total knee arthroplasty

Abstract: Background:This meta-analysis aimed to illustrate the efficacy and safety of combined topical and intravenous (IV) tranexamic acid (TXA) for blood loss control in primary total knee arthroplasty (TKA) patients.Methods:In April 2017, a systematic computer-based search was conducted in PubMed, EMBASE, Web of Science, Cochrane Database of Systematic Reviews, and Google database. Data on patients prepared for TKA surgery in studies that compared combined topical and IV TXA versus placebo, topical, or IV TXA alone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 26 publications
(20 reference statements)
1
18
1
Order By: Relevance
“…[ 24 - 30 ] However, in a recent meta-analysis, the combined use of TXA (both IV and topical) has been shown to be more effective over IV use only. [ 31 ] Consistently, a combined TXA application was carried out in our protocol. However, topical TXA was prepared as a cocktail together with ropivacaine hydrochloride and diclofenac sodium and applied not only by pouring it into the wound but through periarticular injection.…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 - 30 ] However, in a recent meta-analysis, the combined use of TXA (both IV and topical) has been shown to be more effective over IV use only. [ 31 ] Consistently, a combined TXA application was carried out in our protocol. However, topical TXA was prepared as a cocktail together with ropivacaine hydrochloride and diclofenac sodium and applied not only by pouring it into the wound but through periarticular injection.…”
Section: Discussionmentioning
confidence: 99%
“…Yuhui Wang et al concluded that intraarticular injection of tranexamic acid has significant hemostatic effect for TKA surgery and it can effectively reduce the occult blood loss, postoperative drainage volume as well as total blood loss and prevent the incidence of deep venous thrombosis and improve the prognosis in patients of practical application value [12].…”
Section: Discussionmentioning
confidence: 99%
“…Even when tourniquets are used in TKA, there is considerable bleeding and this procedure may even be considered controversial. 3 Zhang et al 4 demonstrated that when the tourniquet is released, fibronolysis is activated at the site, increasing blood loss. 2 …”
Section: Introductionmentioning
confidence: 99%